THE ANALYSIS OF STUDENT’S SATISFACTION TOWARDS SERVICE QUALITY AT INSTITUTE BUSINESS AND INFORMATICS STIKOM SURABAYA - Sulistiowati; Tutut Wurijanto; Henry Bambang Setyawan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2018)
In this globalization era, business competition is thighter in all fields, nevertheless in eduacation field, especially in a university. According to Forlap Dikti, there are 17 state universities and 328 private universities in East Java. Institute Business and Informatics Stikom Surabaya (Stikom Surabaya) is one of the private universities in East Java which has two faculties. They are Technology and Informatics Faculty and Economics and Business Faculty. Technology and Informatics Faculty has some departments. They are Information System Department (S1 SI), Computer System Department (S1 SK), Visual Communication Design Department (S1 DKV), Graphics Design Department (S1 DG), Computer Multimedia Department (DIV KM), and Informatics Management (DIII MI), while Economics and Business Faculty has three departments. They are Management Department (S1 Man), Accounting Department, and Computerized office and Secretarial Department (DIII KPK). In order to win the competition, Stikom Surabaya always tries to evaluate the quality service based on student’s perception as an input to improve the service quality at Stikom Surabaya. Based on the above problem, the research was addressed to analysis student’s satisfaction towards service quality at Stikom Surabaya. this research used quality service theory written by Parasuraman by using five dimensions which are Tangible, Reliable, Responsiveness, Assurance and Empathy. Methode used in this research was Descriptive Statistic. Based on questionnaire distribution to 57 respondents who who were going to graduate, it was obtainned that students felt satisfied towards the quality service in responsiveness dimenstion, Reliable dimension and empathy. While tangible dimension which need to be improved is parking lot